Clomiphene citrate vs letrozole for ovulation induction in subfertile women with polycystic ovary syndrome: a randomized controlled trial - Nazmashamim; Lokeshwari K; Vinodkumarsuresh Basavaradder (Barpeta Obstetrics and Gynaecological Society, 2022)
Objectives: To compare the efficacy of letrozole and clomiphene citrate (CC) for ovulation induction, endometrial thickness and pregnancy rate in subfertile women with polycystic ovary syndrome (PCOS). Material and methods: A prospective randomized clinical trial was conducted from 1st October 2019 to 31st December 2020, in Basaveshwara Medical College Hospital and Research Centre, Chitradurga. A total of 63 participants were allocated into two groups. Group 1 (N=31) received clomiphene citrate 50 mg twice daily, and group 2 (N=32) received letrozole 2.5 mg twice daily. Both study groups were randomly administered CC or letrozole from day 2 to day 6 of a regular menstrual cycle. Transabdominal ultrasonography was done from day 10 till the dominant follicle appeared. Inj. hCG 5000 IU was administered within 24 hrs after the appearance of the dominant follicle. Parameters assessed were ovulation rate - the appearance of dominant follicles, endometrial thickness, and pregnancy rate. Results: Baseline characteristics were comparable between the two groups. The mean endometrial thickness of 7.2 ± 0.61 in the CC group as compared with the letrozole group was 8.06 ± 0.38 (P=0.000). Ovulation rate as assessed by the appearance of the dominant follicle was significantly higher in the letrozole group (22.45 ± 2.21) as compared with the CC group (19.98 ± 1.88). Analysis of pregnancy rate in the two groups showed a higher pregnancy rate of 81% in group 2 compared to 22% in group 1 (P=0.00). Conclusion: This study showed significant improvement in endometrial thickness and pregnancy rates in the letrozole group as compared to CC used for ovulation induction in infertile PCOS. Furthermore, we noted a substantially increased ovulation rate in the letrozole group (P<0.00).